Potential health benefits of carotenoid lutein: An updated review. (August 2021) - Mitra, Saikat; Rauf, Abdur; Tareq, Abu Montakim; Jahan, Shamima; Emran, Talha Bin; Shahriar, Talukder Galeeb; Dhama, Kuldeep; Alhumaydhi, Fahad A.; Aljohani, Abdullah S.M.; Rebezov, Maksim; Uddin, Md Sahab; Jeandet, Philippe; et al.
Abstract: Carotenoids in food substances are believed to have health benefits by lowering the risk of diseases. Lutein, a carotenoid compound, is one of the essential nutrients available in green leafy vegetables (kale, broccoli, spinach, lettuce, and peas), along with other foods, such as eggs. As nutrition plays a pivotal role in maintaining human health, lutein, as a nutritional substance, confers promising benefits against numerous health issues, including neurological disorders, eye diseases, skin irritation, etc. This review describes the in-depth health beneficial effects of lutein. As yet, a minimal amount of literature has been undertaken to consider all its promising bioactivities. The step-by-step biosynthesis of lutein has also been taken into account in this review. Besides, this review demonstrates the drug interactions of lutein with β-carotene, as well as safety concerns and dosage. The potential benefits of lutein have been assessed against neurological disorders, eye diseases, cardiac complications, microbial infections, skin irritation, bone decay, etc. Additionally, recent studies ascertained the significance of lutein nanoformulations in the amelioration of eye disorders, which are also considered in this review. Moreover, a possible approach for the use of lutein in bioactive functional foods will be discussed.